BUILDING ORGANIZATIONAL CITIZENSHIP BEHAVIOR TO IMPROVE EMPLOYEE PERFORMANCE AT PT. AGRO KARUNIA BESTARI - Heriyono, Heriyono; Dhameria, Vita (Jurnal Riset Bisnis dan Manajemen, 2025)
A success of organization in runging its activities is determined by human resources as activity executors. The existence of public organization’s success is defined by the human resources. Researh method employed was purposive sampling with the number of samples were 120 employees of PT Agro Karunia Bestari. The data were analyzed by using Structural Equation Model (SEM) with statistical package AMOS 22. The results of hypothetical testing were (1) Employee engagement and organizational citizenship behavior had a positive and significant influence towards organizational citizenship behavior, (2) Employee engagement a had positive and insignificant influence towards employee performance, (3) Perceived organizational support had a positive and significant influence towards employee performance, and (4) Organizational citizenship behavior had a positive and significant influence towards employee performance.